2013
DOI: 10.4161/psb.23358
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of VOZ2 confers biotic stress tolerance but decreases abiotic stress resistance in Arabidopsis

Abstract: VOZ (vascular plant one zinc-finger protein) is a plant specific one-zinc finger type transcriptional activator, which is highly conserved through land plant evolution. We have previously shown that loss-of-function mutations in VOZ1 and VOZ2 showed increased cold and drought stress tolerances whereas decreased biotic stress resistance in Arabidopsis. Here, we demonstrate that transgenic plants overexpressing VOZ2 impairs freezing and drought stress tolerances but increases resistance to a fungal pathogen, Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 8 publications
5
30
0
Order By: Relevance
“…20,21) In addition, VOZ1 and VOZ2 are involved in changing the expression of various stress-related genes and controlling both abiotic and biotic stress-responsive pathways, such as those related to freezing responses and pathogens. 22,23) Recently, it was reported that the voz1 voz2 mutant is responsive to vernalization. 24) In the present study, we further investigated VOZ function in the regulation of FLC, analyzing the responses to vernalization using voz1 voz2 mutants both in Col and FRI FLC backgrounds.…”
Section: )mentioning
confidence: 99%
“…20,21) In addition, VOZ1 and VOZ2 are involved in changing the expression of various stress-related genes and controlling both abiotic and biotic stress-responsive pathways, such as those related to freezing responses and pathogens. 22,23) Recently, it was reported that the voz1 voz2 mutant is responsive to vernalization. 24) In the present study, we further investigated VOZ function in the regulation of FLC, analyzing the responses to vernalization using voz1 voz2 mutants both in Col and FRI FLC backgrounds.…”
Section: )mentioning
confidence: 99%
“…Both drought and cold stress led to 26S proteasome‐mediated degradation of VOZ2 protein in plants, and voz1voz2 plants exhibit enhanced resistance to these stress conditions. Correspondingly, overexpression of VOZ2 leads to enhanced susceptibility to abiotic stresses (Nakai, Fujiwara, et al, ). Based on these observations, we speculated that BTS may play some role in mediating responses to abiotic stress conditions beyond that of iron deprivation through its interactions with VOZ1/2.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to explore potential new roles for BTS beyond iron homeostasis, we investigated interacting partners of BTS identified through Yeast‐2‐Hybrid analysis (Long et al, ). Of particular interest was VOZ2, a transcription factor involved in both abiotic and biotic stress responses and development and targeted by an as of yet unknown E3 ligase for 26S proteasome‐mediated degradation (Nakai et al, ; Nakai, Fujiwara, Kubo, & Sato, ). Here, we focus specifically on the interaction between BTS and VOZ2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations